Occurrence of freshwater stingrays (Chondrichthyes: Potamotrygonidae) in the Uruguay River and its tributaries, Uruguay, South America. - Oddone, Maria Cristina; Velasco, Gonzalo; Rincon, Getulina (My University, 2008)
Four records of potamotrygonids in the Uruguay River and its tributaries in Paysandu, Uruguay are reported in this paper. The first one was a specimen caught in 1934, of undetermined sex and weighing 120 kg and with a disc width of ca 150 cm. The second specimen, caught in 1998, was also of undetermined sex; it weighed 50 kg total weight and its disc width measured 103 cm. The third specimen was caught in 2001; it was an adult male, weighed 114 kg total weight and its disc width measured ca 110 cm. The fourth one, caught in 2004, was a female, 11 kg in total weight and with a disc width of 80 cm. According to the size and general description, specimens were identified as Potamotrygon brachyura, to date the only potamotrygonid confirmed for Uruguay.